Analisis Hukum Islam Terhadap Tradisi Penentuan Kecocokan Pasangan Menggunakan Weton Dalam Primbon Jawa - 'Uyuunul Husniyyah (MAQASHID Jurnal Hukum Islam, 2020)
Allah SWT. creates every creature with their respective partner with the aim to save offspring. Marriage plays a very important role in protecting future generations. Since the entry of Islam into the Javanese palace, Javanese wedding customs have been combined with the teachings of local beliefs, including animism and dynamism. This combination is used and passed on to future generations to this present time. Many Javanese customary traditions are still used before marriage, for example calculating the wedding day, which is usually carried out during the engagement. The second is calculating the match using weton of the bride and groom. It frequently happens that only because the weton calculations of the bride and groom do not match, they eventually do not get the blessing from both prospective parents. In this paper, the author focused on discussing the perspective of Islamic law on the tradition of determining the match of a partner using weton in Javanese primbon. This study used a qualitative method, by analyzing the concepts or data obtained by using the theories that had been collected. The theories were taken from books, theses, and journals. The results of this study showed that the tradition of determining the match of a partner using the calculation of weton is not allowed because it is against Islamic law. In this case, it is against QS An-Naml: 65, Hadith of Rosulullah SAW., narrated by Ahmad no. 9532, QS an-Nahl: 72, QS ash-Shura: 12, QS at-Taghabun: 11.